1989
DOI: 10.1152/ajprenal.1989.256.3.f414
|View full text |Cite
|
Sign up to set email alerts
|

Na-HCO3 cotransport and Na-H antiporter in chronic respiratory acidosis and alkalosis

Abstract: Renal acidification in renal proximal tubule is thought to be mediated by luminal Na-H antiporter and the HCO3- generated by this antiporter is removed from the cell by a basolateral Na-HCO3 cotransporter. To study the effect of respiratory acid-base disorders on these transport systems, we have measured the Na-HCO3 cotransport in basolateral membranes and Na-H antiporter in luminal membranes in control rabbits, rabbits exposed to 10% CO2 (chronic hypercapnia), and rabbits exposed to 10% O2-90% N2 (chronic hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0
1

Year Published

1990
1990
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 0 publications
4
32
0
1
Order By: Relevance
“…Parallel modulation of apical and basolateral membrane H+/OH-/HCO transporters in response to a variety of conditions has been extensively documented in the proximal tubule. Parallel adaptive increases in apical membrane Na+/H+ antiporter activity and basolateral membrane Na+/3HCO5 cotransporter activity have been found under the chronic conditions of metabolic acidosis (35,36) and alkalosis (35), respiratory acidosis (37,38) and alkalosis (37), hyperfiltration (39), and K+ depletion (40). In addition, acute exposure of the in vitro microperfused proximal tubule to angiotensin II has been found to increase in parallel the activities of these two transporters (41 ).…”
Section: Discussionmentioning
confidence: 85%
“…Parallel modulation of apical and basolateral membrane H+/OH-/HCO transporters in response to a variety of conditions has been extensively documented in the proximal tubule. Parallel adaptive increases in apical membrane Na+/H+ antiporter activity and basolateral membrane Na+/3HCO5 cotransporter activity have been found under the chronic conditions of metabolic acidosis (35,36) and alkalosis (35), respiratory acidosis (37,38) and alkalosis (37), hyperfiltration (39), and K+ depletion (40). In addition, acute exposure of the in vitro microperfused proximal tubule to angiotensin II has been found to increase in parallel the activities of these two transporters (41 ).…”
Section: Discussionmentioning
confidence: 85%
“…Sci. USA 87 (1990) also been found by some investigators to cause an increase in Na/H antiporter activity (15)(16)(17). In the next series of studies, we performed experiments similar to those described above, with the exception that acid medium was identical to control medium, and acid cells were placed in a 10% C02/ 90% air incubator while control cells were placed in a 5% C02/95% air incubator.…”
mentioning
confidence: 87%
“…A number of chronic conditions associated with increased proximal tubular H secretory capacity, including chronic metabolic and respiratory acidosis, chronic K deficiency, and chronic hyperfiltration, are all associated with adaptations in proximal tubular function (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16). These adaptations include increased activities ofthe apical membrane Na/H antiporter and Na/citrate cotransporter, the basolateral membrane Na/3HCO3 cotransporter, phosphatedependent glutaminase, and phosphoenolpyruvate carboxykinase (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). A common feature of these proteins is that they all contribute to net acid excretion, either through acid secretion or ammonia synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Kinetic studies on the transporters have found that substrate affinities are unaffected and Vm. is increased (3,6,8,9,11).…”
Section: Introductionmentioning
confidence: 99%